The core promoter region of the tumor necrosis factor alpha gene confers phorbol ester responsiveness to upstream transcriptional activators. - Leitman, D C (1992)
Activators of protein kinase C, such as 12-O-tetradecanoylphorbol 13-acetate (TPA), are known to regulate the expression of many genes, including the tumor necrosis factor alpha (TNF) gene, by affecting the level or activity of upstream transcription factors. To investigate the mechanism whereby TPA activates the TNF promoter, a series of 5'-deletion mutants of the human TNF promoter linked to chloramphenicol acetyltransferase was transfected into U937 human promonocytic cells. TPA produced a 7- to 11-fold activation of all TNF promoters tested, even those promoters truncated to contain only the core promoter with no upstream enhancer elements. The proximal TNF promoter containing only 28 nucleotides upstream and 10 nucleotides downstream of the RNA start site confers TPA activation to a variety of unrelated upstream enhancer elements and transcription factors, including Sp1, CTF/NF1, cyclic AMP-response element, GAL-E1a, and GAL-VP16. The level of activation by TPA depends on the TATA box structure, since the TPA response is greater in promoters containing the sequence TATAAA than in those containing TATTAA or TATTTA. These findings suggest that the core promoter region is a target for gene regulation by second-messenger pathways.